(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to assess the impact of different rearing site zones with varying temperature–humidity index (THI) on the metabolic regulation of lactating local dairy cows. Materials and Methods: Forty local dairy cows were used in this study, consisting of 20 in rearing sites with THI 66–70 (Pangalengan) and 78–82 (Sumedang), at 950 and 550 m above sea level, respectively. Basal rations were given every morning and evening, consisting of forage and concentrate. Temperature and humidity were recorded daily to determine the average daily THI. Blood samples in both groups of experimental animals were collected according to standard procedures every month during the 4 months of the experiment. Blood analysis followed procedures based on protocols from KIT Randox (UK), using a spectrophotometer. Results: Lipid activity and regulation appeared higher (p < 0.05) in the group of lactating dairy cows kept at THI comfort zone 66–70 than at THI slight stress zone (78–82). Similarly, blood lipid levels were better (p < 0.05) in the cows in the comfort zone (66–70). Conclusion: The study’s results on the impact of the rearing zone of lactating local dairy cows appeared to affect the modulation of lipids in the body. Lipogenesis regulation and metabolism showed higher activity in the group of dairy cows reared in the comfort zone (THI = 66–70) compared to the group of dairy cows reared in the discomfort zone. J. Adv. Vet. Anim. Res., 12(2): 661–667, June 2025 http://doi.org/10.5455/javar.2025.l929